Hybrid Approach for Minimizing Departure Air Traffic Delays Following Standard Instrument Departures (Statistics, Optimization & Information Computing, 2024)
The efficient scheduling of departure air traffic persists as one of the most challenging aspects of air traffic management in recent years. A proper sequencing enhances airport operations, minimises delay, and improves airspace capacity and traffic forecasting. This paper proposes a sequential hybridisation algorithm designed to assist air traffic controllers in determining the optimal departure sequence complying with the standard instrument departures (SIDs).The level of complexity increases when taking into account the departure runway constraints, the configuration of flight paths after takeoff, and the aircraft's operational limits during the takeoff phase. Another challenging aspect is the wide diversity in aircraft types.The suggested approach proposes a Genetic algorithm (GA) strengthened with the Partially Mixed Crossover technique (PMX). The initial population of the GA is enhanced with the Shortest Job First (SJF) method. This sequential hybridisation algorithm dynamically arranges the departure traffic sequence based on their performances and the complexity of the followed SIDs.